A durable half-metallic diatomic catalyst for efficient oxygen reduction. Issue 4 (8th March 2022) - Li, Hongguan; Di, Shuanlong; Niu, Ping; Wang, Shulan; Wang, Jing; Li, Li
Abstract : By elaborately constructing a Fe–Zn based diatomic catalyst, the active center is changed from FeN4– ZnN4 to FeN4– Zn–N2 after protonation, leading to the well-maintained FeN4 structure and thus high stability of ORR. Abstract : Single atom metal–nitrogen–carbon materials have shown immense potential for the oxygen reduction reaction (ORR) while the development of durable catalysts with high reactivity remains a great challenge. Herein, by rationally designing a diatomic catalyst Fe/Zn–N–C based on theoretical screening, we propose a unique half-metallic electronic structure induced by cooperation of Fe and Zn. This structure populates spontaneous spin-polarized conduction electrons at the Fermi level, resulting in an enhancement in free O2 capture and bonding. Meanwhile, the active center of FeN4 is well preserved with Zn–N as the sacrificial bond during the ORR. Fe/Zn–N–C therefore achieved remarkable ORR activities in both acidic and alkaline media as well as impressive long-term durability that outperform most state-of-the-art catalysts and commercial benchmarks. This work advances our fundamental knowledge of the structure–performance relationship for ORR electrocatalysts, which could potentially inspire the exploration of high-performance candidates via electronic structure modulation.